Hydrotalcites as a Promising Adsorbent for Hemicellulose Hydrolysate Detoxification in Xylitol Production - Débora D. V. da Silva; Kelly J. Dussán; Isabela A. L. Costa; Marcus B. S. Forte; Maria G. A. Felipe (Fermentation)
The worldwide demand for sustainable bioprocesses is undeniable, as well as for research aimed at the biotechnological exploitation of lignocellulosic materials, especially their hemicellulosic fractions rich in xylose. Various bioproducts can be obtained from these fractions, although some bottlenecks still exist, such as the presence in hemicellulosic hydrolysates of compounds that are toxic for microorganisms, which requires a previous step of detoxification to reduce them to non-inhibitory levels. The present investigation proposes the use of hydrotalcites as a new detoxifying agent for the hemicellulosic hydrolysate of sugarcane straw to produce xylitol by Candida tropicalis, aiming at a greater removal of phenolics and less loss of sugars. The design of these experiments was used for factorial effect analysis in a simultaneous way; the influences of pH and temperature were evaluated, considering the detoxification process at different times for both uncalcined and calcined hydrotalcite adsorbents. While for the calcined hydrotalcite, the temperature was the significant factor, for the uncalcined, there was also an influence of pH and little effect on the factors of yield and productivity. The effectiveness of hydrotalcites as demonstrated in this research, mainly regarding the ability to reduce the content of phenolic compounds in hydrolysates with a low loss of sugar content, followed by fermentability to produce xylitol, is a strong requirement for the proposition of these new adsorbents in investigations of the development of sustainable technologies for obtaining bioproducts in a biorefinery context.